A review on synthesis of β-amino carbonyl compounds using nanocatalyst - Satyaranjan Behera (Tetrahedron Green Chem)
Nanomaterials have piqued researchers' interest in various fields due to their extraordinary advantages, which include a large surface area. The use of nanomaterials in catalysis is a hot issue for researchers. Catalysis plays a vital role in the synthesis of medicinal as well as pharmaceutical compounds. Pharmaceutical chemicals, including β-amino carbonyl compounds and their derivatives, are commonly used as synthetic intermediates in manufacturing natural products, pharmaceuticals, physiologically active molecules, and medicines. Synthesis of β-amino carbonyl compounds involves many processes, including Mannich and aza-Michael reactions. The synthesis of β-amino carbonyl compounds remains challenging for chemists due to their severe side products. Researchers have now used nanocatalysts to achieve clean and smooth reactions, high purity of products, and reusability. Due to high surface area, nanocatalysts have tremendous catalytic activity. Nowadays many modified nanocatalyst have been developed to produce high yields of the products. The present review described the synthesis of β-amino carbonyl compounds by using different nanocatalysts reported to date.